Examination Malpractice and Teachers’ Productivity in Nigerian Schools: Way Forward - Danbaba, Shuaib Abdullahi; Ogundele, Michael Olarewaju; Ezeuduji, Ifeanyi Chiweike (NIU Journal of Social Sciences, 2018)
The paper examined the baneful effects of examination malpractice on teachers productivity in Nigerian schools: The issues relating to the examination malpractices like the concepts, types of examination malpractices the causes if examination malpractices, the effects on the teachers’ productivity and the way forward were also examined in the paper. It was however concluded that adequate war should be waged against the perpetration of examination malpractice in the interest of enhancing high productivity among the Nigerian school graduates. Keywords: Examination malpractices teachers’ productivity and Nigerian schools.